Analysis Of Students’ Understanding Of Concepts On Fluid Topics - Sihombing, Marlina Septiani (Al-Khazini: Jurnal Pendidikan Fisika, 2025)
Known as a science that studies natural phenomena, therefore learning physics requires the ability to understand physics concepts in all physical materials, especially fluids. However, in reality, students’ ability to understand concepts is still low. This is because most physics learning still uses the lecture method with the help of text and Power Point, but it is rare to find physics learning using experimental methods which can affect students’ level of understanding of physics concepts. This research was conducted on 16 students at one of the high schools in Medan City, SMAS FREEMETHODIST-1 MEDAN using descriptive-quantitative research methods. This research aims to determine the level of understanding of students’ physics concepts on the topic of fluid material which includes static fluids and dynamic fluids as well as analyzing what material sub-topics often become problems for students when learning physics. This research is a quantitative descriptive study using a 10-question three tier instrument about Hydrostatic Pressure, Pascal’s Law, Archimedes’ Law and Bernoulli’s Law Principles. Based on this research, students experienced misconceptions on all fluid sub-topics tested, namely Hydrostatic Pressure with an average of 50% misconceptions and 50% who did not understand the concept. Pascal’s Law with an average of 25% misconceptions and 50% who don’t understand the concept. Archimedes’ Law with an average of 37.5% misconceptions and 62.5% who don’t understand the concept. Bernoulli’s principle with an average of 59% misconceptions and 28% who don’t understand the concept. Keywords: understanding the concept, static fluid, dynamic fluid, three tier